Does Reading Standardized Tests Aloud Meet the Scientific Definition of an Accommodation?. Issue 4 (2nd October 2019) - Spiel, Craig; Evans, Steven W.; Harrison, Judith R.
Abstract: The purpose of this study was to determine if reading a standardized tests aloud is an effective accommodation to address impairment associated with attention-deficit/hyperactivity disorder (ADHD) as demonstrated by a differential boost to those with ADHD relative to same aged typically developing peers and if the size of the differential boost changed over the duration of the test. Participants were 45 children in Grades 5 and 6 (58% with ADHD), who were randomly assigned to take a standardized test in silence or with a recording of the test questions and answer choices read aloud. Results indicated that reading tests aloud significantly improved the testing performance of children with ADHD and provided a differential boost relative to children without ADHD. Implications for practice and future research are discussed.